2023
DOI: 10.1002/cssc.202202188
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the Effect of Activators used in The Synthesis of Biomass‐Derived Carbon Electrocatalysts on the Electrocatalytic Performance for CO2 Reduction

Abstract: N‐doped carbon materials can be efficient and cost‐effective catalysts for the electrochemical CO2 reduction reaction (CO2RR). Activators are often used in the synthesis process to increase the specific surface area and porosity of these carbon materials. However, owing to the diversity of activators and the differences in physicochemical properties that these activators induce, the influence of activators used for the synthesis of N‐doped carbon catalysts on their electrochemical performance is unclear. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 90 publications
0
20
0
Order By: Relevance
“…[17,46,47,51,55,56] Using low-cost, renewable biomass as raw materials, which include proteins (such as hemoglobin, collagen, and so on) and polysaccharides (such as chitin, cellulose, and so on), to synthesize carbon materials for use in electrocatalysis has great potential and advantages. [17,47,48,50,51,[55][56][57] High-temperature pyrolysis of biomass materials has been used to produce carbon materials. [17,47,48,50,51,[55][56][57] These biomass-derived carbon materials preserve the characteristic hierarchical structures and porous nature of the original materials.…”
Section: Advantages Of Biomass-derived Carbon-supported Catalystsmentioning
confidence: 99%
See 2 more Smart Citations
“…[17,46,47,51,55,56] Using low-cost, renewable biomass as raw materials, which include proteins (such as hemoglobin, collagen, and so on) and polysaccharides (such as chitin, cellulose, and so on), to synthesize carbon materials for use in electrocatalysis has great potential and advantages. [17,47,48,50,51,[55][56][57] High-temperature pyrolysis of biomass materials has been used to produce carbon materials. [17,47,48,50,51,[55][56][57] These biomass-derived carbon materials preserve the characteristic hierarchical structures and porous nature of the original materials.…”
Section: Advantages Of Biomass-derived Carbon-supported Catalystsmentioning
confidence: 99%
“…[17,47,48,50,51,[55][56][57] High-temperature pyrolysis of biomass materials has been used to produce carbon materials. [17,47,48,50,51,[55][56][57] These biomass-derived carbon materials preserve the characteristic hierarchical structures and porous nature of the original materials. [47,48,50,51,56,57] The porous morphologies of these carbon carriers facilitate mass transport, and their high specific surface areas provide abundant space for active sites.…”
Section: Advantages Of Biomass-derived Carbon-supported Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Hursán et al prepared N-doped carbon catalysts with different pore sizes via a sacrificial support method and found that the catalysts showed different selectivity, activity, and stability even with similar N-doping content and a similar distribution of N-containing species and no correlation was found between the specific surface area and catalytic performance. In previous work, we also found that there is no significant correlation between the catalytic performance and specific surface area, and N-doping content and that the ratio of mesopores and the degree of graphitization play an essential role . We believe that an over-emphasis on the effects of specific surface area and N-doping level can easily lead to lopsided conclusions, which do not fully reflect the actual structure–performance relationships of N-doped carbon catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…In previous work, we also found that there is no significant correlation between the catalytic performance and specific surface area, and N-doping content and that the ratio of mesopores and the degree of graphitization play an essential role. 30 We believe that an over-emphasis on the effects of specific surface area and N-doping level can easily lead to lopsided conclusions, which do not fully reflect the actual structure−performance relationships of N-doped carbon catalysts. Therefore, to develop better N-doped carbon catalysts for the CO 2 RR, it is necessary to further elucidate the structure−performance relationship of Ndoped carbon materials through a comprehensive and integrated analysis.…”
Section: ■ Introductionmentioning
confidence: 99%